Towards freedom : the African-Canadian experience - Alexander, Ken.; Glaze, Avis. (Toronto : Umbrella Press, 1996)
The book traces the four-hundred-year struggle for freedom, justice, peace, and equality in Canada. Blending historic events and people with contemporary issues, it show black nation-builders contributing enormously to Canda's evolving demoncracy. The border is described as porous, with influences moving to and from the United States, the Caribbean, Africa, with influences moving to and from the United Staes, the Caribbean, Africa, and Europe. The book chronicles these influences, highlights major black achievements, and depicts Canadian history from a black perspective.
Critical Times: The Doctrine of Racial Superiority ; Race Versus Culture ; The Myth Resurfaces ; Shattering the Myth in Black America ; And What About Black Canada? ; History and the Colour Black in North America -- 2. In on the Ground Floor: Slavery and the British Regime ; Black Loyalists and Black Slaves in the Maritimes ; The French and Haitian Revolutions ; Blacks and Native Peoples in Loyalist Canada ; Self-Help and the Exodus of Sierra Leone ; Jamaican Maroons in Canada ; The Abolitionists -- Safe Haven: Myth or Reality?: The Underground Railroad ; Early Black Settlements in British Columbia ; Self-Segregation: the Only Choice? ; The Elgin Settlement and Buxton Mission ; Education and the Buxton Mission ; Dred Scott, John Brown, and Canadian Reactions to American Prejudice -- The Struggle for Education: The US Civil War and its Impact on Black Canada ; The Schooling of Black America After the Civil War ; The "Science" of Race and its Impact ; A Single Drop of Negro Blood and Canada's Missed Opportunity ; Black Educational Reform in the US -- Black Canada: the Dormant Years: Jim Crow and the Reign of Terror ; Black Canada: Towards the Twentieth Century ; Immigration: "Exodusters" and "Sodbusters" ; How did Canada Respond? -- Racism on the Plain: Indian and Black Oklahomans ; "Plain Racism" ; The Political Bind ; Immigration and the Law ; Viewing History Selectively ; Canadian Innovations and the Challenge Ahead -- The Black Community's Quest for Self-Definition: The Story of Africville ; The Rallying Spirit of Nationalism ; The Struggle to Enlist ; The War Years in Black America ; 1920s: the Harlem Renaissance ; Self-Definition and the Leadership Issue ; Strains on Urban Black Culture ; The Brotherhood of Sleeping Car Porters ; The KKK in Canada ; Black Women and the Church ; A Lost Opportunity -- Blacks, Human Rights and Legislation: Racial Discrimination and Canada's Constitution ; The Great Depression and Self-Help ; President Roosevelt and the New Deal ; The Second World War ; The Birth of Human Rights Legislation in Canada ; The Ontario Human Rights Code -- Revolutionary Times in North America: Black Culture Goes Mainstream ; The Desegregation of America's Schools ; "Buying Power": the Montgomery Bus Boycott ; Little Rock, Arkansas ; Sitting, Ridding, and Marching for Freedom ; "I Have a Dream" ; Building a Collective Consciousness in Black Canada -- Immigration: the Next Frontier: The Critical Issue of Immigration ; A Black United Front ; Invoking the Commonwealth ; The West Indian Domestic Scheme ; The Desire to Emigrate ; Canada and the West Indies: a Shared Colonial History ; The Colour-Class Interconnection -- A Context for Change: Shifting Values ; The Divergent Paths of Britain, Canada and South Africa ; Dresden, Amhertsburg, Africville, and North Preston ; A New Mood in Black America ; Malcolm X and the Nation of Islam ; "By Any Means Necessary" ; Shifting Focus: America in Vietnam ; Voter Registration, "Let the Cities Burn," and Black Power ; Black Canadians Respond ; Changes to the Immigration Act: the 1967 "Point System" -- New Black Voices: Immigration and the Test of Multiculturalism ; Trudeaumania vs. Nixon ; The Sir George Williams Incident ; Speaking with One Voice ; An Emerging Black Presence: the Cultural Politics of Caribana ; Political Activism and Setting Down Roots ; "Who Gets In and Who Doesn't" ; Lobbying for Change and the Wisdom of Early Black Civil Rights Strategy ; More Talk about Cultural Diversity and Race Relations ; The 1982 Canadian Charter of Rights and Freedoms ; Post-1967 Black Education in Canada ; The Black Education Lobby -- To the Future: Black Cultural Expression ; The Growing Black Complexion of Canadian Sport ; Passing the Test ; Black Women on the Rise ; Always at the Crossroads ; Whither Goes the African-Canadian Community?
Includes bibliographical references (pages 281-284) and index.
NLJCols20082021
Keywords: Blacks -- Canada -- History; Blacks; Black Canadians -- History; Noirs -- Canada -- Histoire; Canada; History